HUMAN EXPOSURE ASSESSMENT TO MERCURY THROUGH HAIR ANALYSIS IN COASTAL VILLAGES OF THE VALPARAISO REGION (CHILE) - Manuel A. Bravo; Sonnia Parra; Waldo Quiroz; Alexander Neaman (Journal of the Chilean Chemical Society, 2019)
In the present study, we assessed mercury exposure of residents of different sites of Valparaiso Region (Chile) due to fish consumption and atmospheric contamination from coal-burning power plant and copper smelter. Total mercury concentration was determined in 199 hair samples and in 14 species of marine fish, purchased in the supermarket or collected in the studied fishing villages. The total mercury (THg) concentrations ranged from 0.04 to 1.78 μg g-1 in human hair samples and from 0.04 to 3.87 μg g-1 in fish samples. Importantly, hair mercury concentration was significantly higher in the case of population exposed to mercury exclusively by fish consumption (e.g. Quintay and Zapallar), in comparison to the residents exposed to industrial emissions and fish consumption (e.g. Puchuncavi, Las Ventanas, Quintero). Finally, high mercury concentrations were observed in fish types commonly consumed by the residents of the fishing villages, evidencing human exposure to mercury through fish consumption.